2014
DOI: 10.1007/s12350-014-9971-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and operator variability of myocardial blood flow and reserve measurements with 99mTc-sestamibi quantitative dynamic SPECT/CT imaging

Abstract: MBF and reserve measurements using (99m)Tc-sestamibi on a traditional, two-headed camera with fast rotation and with quantitative dynamic SPECT appears to be feasible, warranting further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 43 publications
1
43
0
1
Order By: Relevance
“…Since there is another risk of contamination in this 9 non-CAD patients. Third, we did not correct the baseline flow values for the rate-pressure product, thus our data was highly variable compared to other studies (8,9). Forth, we need to acquire the image for 4 times in this protocol, which may interfere throughput of the test.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Since there is another risk of contamination in this 9 non-CAD patients. Third, we did not correct the baseline flow values for the rate-pressure product, thus our data was highly variable compared to other studies (8,9). Forth, we need to acquire the image for 4 times in this protocol, which may interfere throughput of the test.…”
Section: Discussionmentioning
confidence: 97%
“…Earlier studies suggested the possibility of quantifying the MFR on dynamic planar acquisition following conventional SPECT acquired with conventional SPECT cameras (6,8,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 It does not directly mean that it can be accepted as a clinical tool in daily practice. Measuring MBF and CFR by cardiac PET is a mature technology but is not widely used in clinics.…”
Section: Measurement Of Mbf and Cfrmentioning
confidence: 99%
“…In recent years, several different SPECT system designs have become available that do not physically rotate around the patient, but rather collect data simultaneously from all projections over a 1808 arc about the patient's thorax. 14 While it is possible to quantify myocardial blood flow from dynamic SPECT data acquired with a conventional rotating Ager camera, 15 the advent of the newer SPECT system designs, and especially those incorporating solid state detectors for which counting efficiency is 3-5 times that of conventional Anger cameras, 14 have the prospect of enabling absolute quantification of myocardial blood flow derived from dynamic SPECT acquisitions, such as with agents such as T-99m-tetrofosmin, 16 in a manor analogous to the way in which rest/stress Rb-82 PET dynamic data currently are used to quantify blood flow. If that is the case, additional QA data processing procedures will be needed, including those designed to verify correct timing of bolus injections, adequacy of tracer delivery, and sufficiency of radiotracer curve clearance.…”
mentioning
confidence: 99%